Mineral Mixture Feeding Enhances Dairy Animals Productivity: A Study of Bihar, India - Singh, Dhiraj Kumar; Sahu, Shree P.; Teufel, Nils (Indian Journal of Animal Nutrition, 2020)
Dairying is not only an integral part of small-holder farming system, but it is also providing a significant source of livelihood for landless households in Bihar, India. A shift in the contribution by different sectors to the State Gross Domestic Product (SGDP) in Bihar has been observed as contribution of livestock sector has increased from 22 to 40 percent and at the same time agriculture sector contribution has decreased from 45 to 20 percent during last two decades. The per-capita milk availability in Bihar is meager (239 g/d) compared to India’s average (375 g/d) in 2017-18 as productivity of animals is low due to poor feeding based on crop residue and limited concentrates. The present study was carried out on 510 dairy animals to examine the effects of mineral mixture on livestock productivity in Bihar. After introducing (50 grams) mineral mixture in the feed, average milk yield, fat and SNF content increased by 6.2%, 5.3% and 1.8%, respectively. Feeding mineral mixture to dairy animals, milk yield increased by 0.49 L/d/animal.  At the same time fat content and SNF content also increased by 0.20 and 0.15 points.  On average, farmers benefitted from increased net profits by ₹15.8/d/animal.  It shows that the dairy farmers can increase their revenue from increased milk sales in terms of higher quantity (yield) and quality (fat and SNF). The mineral mixture feeding also showed positive effects on health and reproductive performance in terms of animal appearance and, timely conception and least incidence of ectoparasites.